Wavelet Based Demodulation of Vibration Signals Generated by Defects in Rolling Element Bearings - C.T. Yiakopoulos; I.A. Antoniadis (Shock and Vibration)
Vibration signals resulting from roller bearing defects, present a rich content of physical information, the appropriate analysis of which can lead to the clear identification of the nature of the fault. The envelope detection or demodulation methods have been established as the dominant analysis methods for this purpose, since they can separate the useful part of the signal from its redundant contents. The paper proposes a new effective demodulation method, based on the wavelet transform. The method fully exploits the underlying physical concepts of the modulation mechanism, present in the vibration response of faulty bearings, using the excellent time-frequency localization properties of the wavelet analysis. The choice of the specific wavelet family is marginal to their overall effect, while the necessary number of wavelet levels is quite limited. Experimental results and industrial measurements for three different types of bearing faults confirm the validity of the overall approach.